Pola Komunikasi Orang Tua terhadap Anak Autisme: Systematic Literature Review - Suargani, Ganjar; Sri Maullasari; Nora Apriliana (Indo-MathEdu Intellectuals Journal, 2025)
Autism is a condition that often causes parents to feel worried and need to give extra attention. Children with autism have difficulty communicating and interacting with others, as well as with their imagination. This article discusses the ways parents use to communicate with children with autism. This paper uses a literature review approach. The data sources are journals relevant to the topic, obtained through a search using the keywords “parent communication” and “autism.” The data sources were obtained from national journals with quantitative and qualitative research designs, ranging from 2011 to 2024 from the Google Scholar website, with a total of 26 articles and 14 articles meeting the criteria. The articles were analyzed through a process of identification, eligibility, and screening. The results of the analysis showed that children with autism need continuous support and intensive assistance from their families. Two-way communication patterns proved to be more effective in supporting the development of autistic children. In addition, each family member has an important role in establishing conducive communication to support the development of autistic children in the family environment.